웹 서버 구성을 통한 가상머신과 컨테이너 방식 비교 분석 - 배유미; 정성재; 소우영; Bae, Yu-Mi; Jung, Sung-Jae; Soh, Woo-Young (한국정보통신학회논문지, 2014)
The technique of virtual machine construction using hypervisor such as Xen and KVM is mainly used for implementation of cloud computing infrastructure. This technique is efficient in allocating and managing resources compared to the existing operation methods. However it requires high resource usage when constructing virtual machines and results in wasting of resources when not using the allocated resources. Docker is a technique based on the container method to resolve such a problem. This paper shows the container method such as Docker is efficient as a web construction technique by comparing virtual machine method to container method. It is shown to be especially useful when storing data into DB or storage devices in such environments of web server or program development. In the upcoming cloud computing environment the container method such as Docker is expected to improve the resource efficiency and the convenience of management. Xen, KVM 등과 같은 하이퍼바이저를 이용한 가상 머신 생성 기술이 클라우드 인프라 구성에 주로 사용되고 있다. 이 기술은 기존의 운영 방식에 비해 자원을 할당하고 관리하는 측면에서는 효율적이다. 그러나, 이 기술은 가상머신 생성시에 높은 자원의 사용량이 요구되고 할당된 자원을 사용하지 않는 경우에는 또 다른 자원의 낭비를 초래한다. 이러한 문제점을 해결하기 위한 방법이 컨테이너 기반의 Docker이다. 본 논문은 가상 머신 방식과 컨테이너 방식을 비교하여 웹 서버 구축 기술로 Docker와 같은 컨테이너 방식이 효율적임을 보여준다. 특히, 웹 서버나 프로그램 개발 환경과 같이 데이터를 데이터베이스나 스토리지 등에 저장하는 경우에는 유용한 것으로 분석되었다. 앞으로의 클라우드 환경에서 Docker와 같은 컨테이너 방식이 자원의 효율성과 관리의 편의성을 더욱 높일 수 있을 것으로 기대된다.